2017
DOI: 10.1136/bmjopen-2017-016571
|View full text |Cite
|
Sign up to set email alerts
|

Priorities for research in miscarriage: a priority setting partnership between people affected by miscarriage and professionals following the James Lind Alliance methodology

Abstract: ObjectivesTo identify and prioritise important research questions for miscarriage.DesignA priority setting partnership using prospective surveys and consensus meetings following methods advocated by the James Lind Alliance.SettingUK.ParticipantsWomen and those affected by miscarriage working alongside healthcare professionals.ResultsIn the initial survey, 1093 participants (932 women who have experienced miscarriage, 8 partners, 17 family members, friends or colleagues, 104 healthcare professionals and eight c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
62
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 16 publications
0
62
0
Order By: Relevance
“…The JLA have developed a step-by-step guide outlining the processes and methods involved in developing priority setting partnerships (PSP) to systematically identify and prioritise unanswered questions in health research. 28 These guidelines are well-established, can be adapted to meet the specific requirements of a PSP, and have been applied to more than 50 PSPs to date across many different health topics, including treatment uncertainties for acne, 29 research into miscarriage, 30 and to identify research priorities for depression, 31 bipolar disorder, dementia and schizophrenia. These JLA Guidelines were adhered to for this digital mental health PSP.…”
Section: Methodsmentioning
confidence: 99%
“…The JLA have developed a step-by-step guide outlining the processes and methods involved in developing priority setting partnerships (PSP) to systematically identify and prioritise unanswered questions in health research. 28 These guidelines are well-established, can be adapted to meet the specific requirements of a PSP, and have been applied to more than 50 PSPs to date across many different health topics, including treatment uncertainties for acne, 29 research into miscarriage, 30 and to identify research priorities for depression, 31 bipolar disorder, dementia and schizophrenia. These JLA Guidelines were adhered to for this digital mental health PSP.…”
Section: Methodsmentioning
confidence: 99%
“…Seven research priority setting studies were identified. [8][9][10][11][12][13][14] An additional four research priority setting studies were identified in the James Lind Alliance database. [15][16][17][18] A further research priority setting study was identified through personal communication with the clinical lead.…”
Section: Resultsmentioning
confidence: 99%
“…19,20 Eight completed and four progressing research priority setting studies were included (Tables 1 and S1). [8][9][10][11][12][13][14][15][16][17][18][19] The PSP for infertility has established the top ten research uncertainties for male infertility, female and unexplained infertility, medically assisted reproduction, and ethics, access, and organisation of care, in a single initiative. 21 Four research priority setting studies have reported their full results in a peerreviewed publication.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a distinct lack of efficacious therapeutic options because of failure of adequate stratification to distinguish these in published studies. Patient-led priority setting groups have highlighted effective interventions to prevent miscarriage as the highest priority in this area (5). This points to a need for a novel approach to therapeutic interventions and suggests the importance of ongoing exploration into immunological RPL.…”
Section: Treating Immunologic Aspects Of Recurrent Pregnancy Lossmentioning
confidence: 99%